Assessment of Functional Properties and Safety Indicators of Amaranth Flour Grain Bread - Nadezhda N. Alekhina; Elena I. Ponomareva; Irina M. Zharkova; Andrej V. Grebenshchikov (Техника и технология пищевых производств)
Introduction. Various formulations of sprouted grain breads, including those with amaranth flour, were developed to combat food-related diseases. Healthy food industry requires thorough assessment procedures and hygienic practices. The research objective was to assess the functional properties and safety indicators of amaranth bread made from sprouted wheat grain. Study objects and methods. One day old grain bread was tested for antioxidant activity using amperometric method. Its glycemic index was determined according to the ratio of the area under the glycemic curve per bread sample to the area under the glycemic curve for pure glucose, expressed as a percentage. Crumb proteins digestibility was measured in vivo using ciliates Paramecium caudatum. Phytin content was measured by the colorimetric method, while safety indicators were compared to the Technical Regulations of the Customs Union No. 021/2011. Bound moisture content was determined with a refractometer after three days of storage according to the change in sucrose concentration. The number of mesophilic aerobic and facultative anaerobic microorganisms (NMAFAnM) was described based on State Standard 10444.15-94. Results and discussion. The amaranth flour slightly affected the antioxidant activity of the grain bread. It decreased the glycemic index by 8.3% and increased the microbiological purity by 1.4 times, raised the crumb proteins digestibility by 3.0%, reduced the phytin content by 7.0%, and slowed down the staleness process by 12 h. In terms of safety indicators, the obtained sample of amaranth grain bread met the TR CU 021/2011 requirements «On food safety». The decrease in the glycemic index values could be explained by the lower activity of amylolytic enzymes in amaranth flour compared to sprouted wheat. The low digestibility of carbohydrates resulted from their effect on starch. The increase in digestibility and the decrease in phytin content were caused by the lower amount of dietary fiber. The high content of bound moisture explains the longer shelf life. Amaranth flour had lower microbiological contamination compared to wheat, which decreased the NMAFAnM. Conclusion. Amaranth flour had a positive effect on the functional properties of grain bread safety indicators, which makes it possible to include it into sprouted wheat grain products.